Spatial language and dialogue - Coventry, Kenny R.; Tenbrink, Thora, 1969-; Bateman, John A. (Oxford : Oxford University Press, 2009)
This text considers how people talk about the location of objects and places. It reports on the developments in the field of spatial language and sets an agenda for future research on spatial conceptualization and communication in cognitive science, computer science, psychology, and linguistics.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Dialogue analysis; Space and time in language